جهود عبد الرحمان الحاج صالح في اللسانيات الحاسوبية والمصطلح الحديث Abdul Rahman Al Haj Saleh's Efforts In Computational Linguistics And The Modern Term - تاحي بختة . (Université de M'sila, 2020)
ملخص: يعدّ الاصطلاح أو المصطلح مفتاح العلوم على حدّ تعبير الخوارزمي، حيث أدّى دورا كبيرا في القديم، وكان يسمّى بـ" مصطلح الحديث"، وكذلك لا يزال يمثل دورا كبيرا وهاما في مختلف العلوم والفنون وشتّى المجالات والميادين. حيث أصبح يهدف البحث في المجال المصطلحي في المقام الأول إلى كشف المصطلحات الحاملة للمعرفة المتخصصة، وتكمن وظيفيته في نقل المعرفة بشتّى أنواعها وأشكالها والمتعلقة بالاستعمال المصطلحي الذي ينتمي إليه كل مجال من المجالات ومما يجب على الباحث في المصطلحات أن يعرفه عن هذا الأخير، من مرجعيات وموسوعات وكذلك مقالات متخصصة لأجله. كما أننا لا ننسى دور اللسانيات في وضع المصطلحات وتنميطها وفهرستها، كما لا نغفل الدور الذي قام به العلامة الجزائري " عبد الرحمن الحاج صالح" لأجله هو الآخر من خلال مشاريعه وكتبه القيمة نذكر منها: كتاب { بحوث ودراسات في اللسانيات العربية}، بأجزائه الثلاثة، وكذلك مشروع " الذخيرة العربية". من خلال هذا يمكننا طرح الإشكال التالي: ما علاقة اللسانيات بالمصطلح؟ وفيما تكمن جهود " عبد الرحمن الحاج صالح"؟. Abstract: The term or term is considered the key to science in the words of Al-Khwarizmi, as it played a great role in the ancient, and was called the term “hadith”, as well as still represents a large and important role in various sciences and arts and in various fields and fields. As research has become aimed in the terminological field in the first place to reveal the terms that carry specialized knowledge, and its function lies in transferring knowledge of various kinds and forms related to the terminological use to which each field belongs and what the researcher in terminology must know about the latter, from references and encyclopedias As well as specialized articles for him. Likewise, we do not forget the role of linguistics in developing, standardizing and indexing terminology, nor do we lose sight of the role played by the Algerian scholar, "Abd al-Rahman al-Hajj Saleh" for his sake, through his projects and valuable books, including: The book {Research and Studies in Arabic Linguistics}, with its three parts. As well as the project "Arab ammunition". Through this we can pose the following problem: What is the relationship of linguistics to the term? As for the efforts of "Abdul Rahman Al Haj Saleh"?
Keywords: الكلمة المفتاحية ; كلمات مفتاحية: المصطلح.، العمل المصطلحي.، اللسانيات.، عبد الرحمن الحاج صالح.